(3LegQI fSH bQjTs - (3GdRHjQj , eUYH Hf YHO Gddg Hf eUYH Hf KGHJ Hf YHO Gddg Hf GdRHjQ, CHh YHO Gddg,J (B236 (3g` s
(3ChdgG (B:s
(3CNHQfG eMeO Hf eYGhjI Hf YHO GdQMef bGd MOKfG CHh GSMGb Hf ehSi Hf Lejd GdCfOdSi HeUQ s
(3BNQgG (B:s
(3bJd cQR gPG eY QShd Gddg Udi Gddg Ydjg hSde jhe aJM ecI gPG BNQ LegQg bQjT hGdMeO ddg Ydi Yhfg Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B248 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B291s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(1023) s
Keywords: (3GdJGQjNs